Aging and Sex Influence Cortical Auditory-Motor Integration for Speech Control - Li, Jingting; Hu, Huijing; Chen, Na; Jones, Jeffery A.; Wu, Dan; Liu, Peng; Liu, Hanjun (Frontiers in Neuroscience, 2018)
It is well known that acoustic change in speech production is subject to age-related declines. How aging alters cortical sensorimotor integration in speech control, however, remains poorly understood. The present event-related potential study examined the behavioral and neural effects of aging and sex on the auditory-motor processing of voice pitch errors. Behaviorally, older adults produced significantly larger vocal compensations for pitch perturbations than young adults. At the cortical level, there was a significant interaction between aging and sex on the N1-P2 complex. Older males adults produced significantly smaller P2 amplitudes than young males, while young males produced significantly larger N1 and P2 amplitudes than young females. In addition, females produced faster N1 responses than males regardless of age, while young adults produced faster P2 responses than older adults across the sexes. These findings provide the first neurobehavioral evidence that demonstrates the aging influence on auditory feedback control of speech production, and highlight the importance of sex in understanding the aging of the neuromotor control of speech production.